2011
DOI: 10.1080/09585192.2011.538971
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between expatriate job level and host country national categorization: an investigation in the UK

Abstract: Using data from 493 host country nationals (HCNs) in the UK, we investigated relationships between expatriate gender, national origin, and job level, and HCN characteristics and willingness to help expatriates. Results showed that HCNs from the UK are likely to categorize expatriates as in-group or out-group members based on perceived values similarity, ethnocentrism, and collectivism. This categorization is also likely to affect HCN willingness to provide role information and social support to expatriates. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 36 publications
(45 reference statements)
2
55
0
Order By: Relevance
“…In this connection, Caligiuri (2000) reported that casual interaction between expatriates and HCNs may not be enough of a trigger for the HCN to share role information or cultural insights. Instead, as we noted earlier, it has been argued that HCNs would be likely to share information only with expatriates toward whom they experience high interpersonal affect -in other words, expatriates they like (Varma et al, 2009;Varma et al, 2011b).…”
Section: Importance Of Role Information and Social Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…In this connection, Caligiuri (2000) reported that casual interaction between expatriates and HCNs may not be enough of a trigger for the HCN to share role information or cultural insights. Instead, as we noted earlier, it has been argued that HCNs would be likely to share information only with expatriates toward whom they experience high interpersonal affect -in other words, expatriates they like (Varma et al, 2009;Varma et al, 2011b).…”
Section: Importance Of Role Information and Social Supportmentioning
confidence: 99%
“…As we noted earlier, HCNs will typically share role information with, and offer social support to, only those expatriates whom they like (see, e.g., Varma, et al, 2011b). The other expatriates may be left out of the information circle, either due to their gender and/or national origin, or simply the fact that they are expatriates, which is quite problematic, as all expatriates need role information and social support to successfully adjust to the new location.…”
Section: The Chinese Context and Collectivismmentioning
confidence: 99%
See 1 more Smart Citation
“…EMNCs notwithstanding the handicaps are able to do well (Thite et al, ) owing to their ability to successfully tap the bottom‐of‐pyramid market and being agile in uncertain and dynamic environments. Multinational organizations operating in India have often come up with disruptive business models given the challenges of price and access and uncertainty they have to face (Varma, Shaun, & Budhwar, ). As is obvious from the research presented on EMNCs, there is a need to empirically flesh out the advantages and disadvantages that EMNCs face, and indigenous ways for them to overcome the hurdles and capitalize on the strengths.…”
Section: Internationalization Of Indian Firmsmentioning
confidence: 99%
“…One stream of research tries to explain why local employees might not support expatriates from the angle of ethnic (dis)similarity in expatriate‐local employee interactions. Researchers have found that ethnic dissimilarity can trigger out‐group categorization, which could damage trust and inhibit interpersonal support, information sharing, and cooperative behaviors (Mäkelä, ; Toh & DeNisi, ; Varma, Pichler, & Budhwar, ). These findings align with self‐categorization theory, suggesting in‐group categorization facilitates interpersonal interactions (Brewer & Pierce, ).…”
Section: Introductionmentioning
confidence: 99%